The Nexus Between CO2 Emission, Economic Growth, Trade Openness: Evidences From Middle-Income Trap Countries - Galvan, Lisette Paola Cervantes; Bhatti, Uzair Aslam; Campo, Carlos Carmona; Trujillo, Ricardo Antonio Simancas (Frontiers in Environmental Science, 2022)
Middle-income countries are currently undergoing massive structural changes toward more industrialized economies. In this paper, we carefully examine the impact of these transformations on the environmental quality of middle-income countries. This study analyses the long-term effects of economic growth, trade, foreign direct investment (FDI) and gross domestic product (GDP) on carbon dioxide (CO2) emissions in Latin American countries that are in the middle-income trap (MIT). Using annual time-series data for the period 2000–2020, the results of middle-income countries of Latin America are compared with higher-income countries (Singapore, the USA, and South Korea) and an upper-middle-income country, China. Specifically, we examine the role of sector value addition to GDP on the CO2 emission nexus for middle-income economies, controlling for the effects on GDP, FDI, and trade. Using regression and path analysis (multiple regression) we find that for higher-income countries FDI, GDP and trade are the important variables that have a strong positive impact on CO2 emission, but that positive impact is weak in MIT countries, which makes this study significant as it highlights important variables needed for MIT countries to remain focused. Autoregressive distributed lag (ARDL) model results also explore that FDI, GDP growth and trade variables can significantly accelerate the environmental quality by CO2 emission, while tourism/travel services and education do not much impact the environment. Hence, our paper provides solid ground for developing a sustainable and pro-growth policy for MIT countries because they are plagued by the decline or stagnation of economic growth, unfair domestic industrial structure, and serious polarization between the rich and the poor. However, due to different international environments, different specific national conditions, and different development policies adopted by each country, the route to escape the MIT varies. Transforming the model of economic growth and realizing sustainable economic development is a crucial way for a country or region to escape from the "trap" of economic stagnation. In the final section, we present the main policy gaps in Latin American countries according to their unique characteristics and recommend policies with suggestions for avoiding the MIT by comparing their economies with those of high-income countries.